2022
DOI: 10.18203/2349-3259.ijct20222656
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrotherapy according to Halliwick concept on children with cerebral palsy and the evaluation of their balance: a randomised clinical trial

Abstract: <p><strong>Background:</strong> Hydrotherapy according to Halliwick concept is a physiotherapeutic intervention technique for disabled patients and for children with neurodevelopmental disorders. Assessing the balance in children with cerebral palsy (CP) is an extremely complex process and more difficult to evaluate the results of some therapeutic interventions in these patients. The purpose of this study is to investigate the effect of Halliwick based Hydrotherapy on the support base in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Their 8-week aquatic interventions showed significantly improved locomotor and object control skills in both the Halliwick and the swim technique group, compared to the controls doing sports as usual. This is consistent with studies that have reported improvements in balance and motor skills after an aquatic intervention in children and adults with neurological disorders (Carroll et al, 2020;Chandolias et al, 2022;Fatorehchy, 2019;Montagna et al, 2014;Terrens et al, 2020;Veldema & Jansen, 2021). These findings are valuable as they suggest a positive transfer of learned water-related motor skills to land-related balance and locomotion which, in turn, can contribute to reducing the risk of motor impairments in children with ASD (Mickle et al, 2011;Stins & Emck, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Their 8-week aquatic interventions showed significantly improved locomotor and object control skills in both the Halliwick and the swim technique group, compared to the controls doing sports as usual. This is consistent with studies that have reported improvements in balance and motor skills after an aquatic intervention in children and adults with neurological disorders (Carroll et al, 2020;Chandolias et al, 2022;Fatorehchy, 2019;Montagna et al, 2014;Terrens et al, 2020;Veldema & Jansen, 2021). These findings are valuable as they suggest a positive transfer of learned water-related motor skills to land-related balance and locomotion which, in turn, can contribute to reducing the risk of motor impairments in children with ASD (Mickle et al, 2011;Stins & Emck, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in agreement with our study regardless of age. A beneficial effect of the Hallwick aquatic method on sitting, walking, running & jumping activities compared to conventional exercises might be attributed to the fact that children engaged in aquatic activities using the Halliwick Concept learn on their own and, they always work at one to one with a personal instructor who knows when and how to progress [22]. Besides, the Halliwick concept teaches independence allowing the child to move and swim without the help of others, which contributes to improving self-esteem and self-awareness [29].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the Halliwick concept teaches independence allowing the child to move and swim without the help of others, which contributes to improving self-esteem and self-awareness [29]. Children may see the activity on water as a recreational or sporting activity, increasing adherence to the program [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation